2019
DOI: 10.1017/s0033291719001818
|View full text |Cite
|
Sign up to set email alerts
|

Emotional instability as a trait risk factor for eating disorder behaviors in adolescents: Sex differences in a large-scale prospective study

Abstract: Background Temperament and personality traits, including negative emotionality/neuroticism, may represent risk factors for eating disorders. Further, risk factors may differ by sex. We examined longitudinal temperament/personality pathways of risk for purging and binge eating in youth stratified by sex using data from a large-scale prospective study. Methods Temperament, borderline personality features, sensation seeking, ‘big five’ personality factors, and depressive symptoms were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 34 publications
6
32
1
Order By: Relevance
“…In accordance with previous studies (Atiye et al, ; Brown et al, ; Martin et al, ; Sutin et al, ), we found an association of higher negative affectivity in early adolescence and the later development of eating pathology. Despite the low number of formal eating disorder diagnoses in our study, the associations were generally robust.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In accordance with previous studies (Atiye et al, ; Brown et al, ; Martin et al, ; Sutin et al, ), we found an association of higher negative affectivity in early adolescence and the later development of eating pathology. Despite the low number of formal eating disorder diagnoses in our study, the associations were generally robust.…”
Section: Discussionsupporting
confidence: 93%
“…In comparison with the number of reports on temperament and weight problems, the literature on prospective studies of temperament and eating disorders (EDs) is scarce (Atiye et al, ; Brown, Hochman, & Micali, ; Stice, South, & Shaw, ). Higher negative affectivity was found to be associated with all EDs (anorexia nervosa [AN], bulimia nervosa [BN], binge‐eating disorder [BED], and eating disorders not otherwise specified [EDNOS]) in a 2015 meta‐analysis of cross‐sectional studies (Atiye et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical symptoms such as restlessness, fatigue, tension, and irritability might either be diffuse, behavioral indicators of psychopathology, specific physical symptoms of anxiety, or, in some cases, might index parental misinterpretation of symptoms. Mechanisms behind this pattern of risk are unclear; it is possible that such symptoms represent early signs of difficulties with emotion regulation (Brown, Hochman, & Micali, ; Castellanos‐Ryan et al., ) or it may be that physical symptoms are more easily observable to parents and thus, more likely to be reported. There was some support for this interpretation in the current sample.…”
Section: Discussionmentioning
confidence: 99%